KEDUDUKAN PEMEGANG HAK JAMINAN DAN KOMPETENSI PERADILAN PAJAK DALAM PENAGIHAN PAJAK - AHMAD RIZKI SRIDADI (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
This research paper is aimed to examine legal problems arising out of conflicting rights concerning private rights owned by holders of security rights and public rights owned by state through Directorate General of Tax under the Ministry of Finance of Republic of Indonesia. This kind of legal problems occurred due to the tax (payable tax) collectivity conducted by Indonesia Directorate General of Tax against goods secured by guarantee rights (mortgage right, hypothecation, fiduciary right, and pawn). First chapter elaborated on legal matters which could be imposed by tax collectivity. Research continued to which of the two (private rights and public rights) would obtain priority right satisfaction of the secured goods if such goods are sold caused by bankruptcy or default by debtor. Another problem was whether Directorate General of Tax could be included as creditor or not. Further problem continued to the competency of the court which stood for different legal authority to examine and to settle this kind of case. According to this research tax obligation had highest position in all legal obligations hierarchy. Thereafter, settlement of this dispute lied on tax court. Role of tax court depended on whether or not process server of tax has implemented immediate and whole collectivity at time of obtaining two matters namely seizure of goods of tax payer by third parties or indications of bankruptcy.